Sistem Informasi Penerimaan Siswa Baru Pada Sekolah Menengah Atas Negeri Punung - ., Sulistianingsih; ., Sukadi (Fakultas Teknologi Informatika Universitas Surakarta, 2014)
Description: Acceptance of new students is one of the processes that exist in educational institutions such as the SMA City of Punung. New admissions process in a town of Punung SMA been performed conventional or without such computerized participant registration data is stored only on paper, conventional counting test scores to determine admission of new students, as well as the announcement of acceptance only informed through the school notice board. Will require a new student information system acceptance in the town of Punung SMA computerized to solve the above problems. This application was built by using the programming language PHP . There are several stages in the development of this application, namely the analysis phase, design, testing, and implementation. This application uses the system design by using Data Flow Diagrams And with MySQL database. Hopefully with this application, the school and prospective students will be facilitated in the new admissions process SMA City of Punung. And these applications can be expected to also be an example to other schools in the application of technology to new admissions process. Keywoards : Acceptance of new student,information system Deskripsi: Proses penerimaan siswa baru di SMA Negeri Punung selama ini dilakukan secara konvensional atau tanpa terkomputerisasi seperti data pendaftaran peserta hanya disimpan di kertas, penghitungan nilai tes secara konvensional untuk menentukan penerimaan siswa baru, serta pengumuman hasil penerimaan hanya diinformasikan melalui papan pengumuman sekolah. Maka diperlukan sebuah sistem informasi penerimaan siswa baru pada SMA Negeri Punung yang terkomputerisasi untuk menyelesaikan permasalah diatas. Aplikasi ini dibangun dengan menggunakan pemrograman PHP . Ada beberapa tahap dalam pengembangan aplikasi ini, yaitu tahap analisis, desain, pengujian, dan implementasi.Aplikasi ini menggunakan desain sistem dengan menggunakan Data Flow Diagram dan dengan database MySQL. Diharapkan dengan adanya aplikasi ini, pihak sekolah serta calon siswa akan dimudahkan dalam proses penerimaan siswa baru SMA Negeri Punung. Dan diharapkan pula aplikasi ini dapat menjadi contoh untuk sekolah lain dalam penerapan teknologi untuk proses penerimaan siswa baru. Kata kunci : Penerimaan Siswa Baru, sistem informasi